PENENTU TINGKAT HUTANG PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rusmanto, 11.42.02.0053 Rusmanto (Students Journal of Economic and Management, 2013)
This study aimed to examine the effect of the independent variables of profitability, asset structure, firm size, firm growth, and non-debt tax shield against leverage. The sampling technique used was purposive sampling at manufacturing companies which listed on the Indonesia Stock Exchange from 2009 to 2011.Â  In total, 88 companies that made profits for three consecutive years obtained as a sample. The data used in this study are secondary data from the Indonesia Stock Exchange, derived from the financial statements of listed manufacturing companies in the period of 2009 to 2011. The analysis technique used is multiple linear regressions. During the observation period of observational data indicates that the number of 264 samples were obtained a number of 239 samples were ready to be processed after the data outliers removed. Based on the results of the study, there were no variables that deviate from normality test and the classical assumption test. The analysis of the data showed that the profitability showed a significant negative effect on leverage. Company Size, non-debt tax shield showed a significant positive effect, negative asset structure is not significantly effect on leverage, while positive firmsâ growth is not significantly effect on leverage. Keywords : Pecking Order Theory, leverage, profitability, asset structure, firm size, firm growth, and non-debt tax shield.